Foreign body in the nasopharynx of a child - Sengupta, Arunabha (Springer India, 2005)
Introduction of foreign body into the nasal cavity of the children by themselves is very common, but lodgment of foreign body in the nasopharyux following introduction through mouth is unusual. Here a case is presented from the Otorhinolaryngology department of S.S.K.M. Hospital, Kolkata, where a child was brought by their parents with history of introduction of a metallic foreign body in the mouth of the child by himself and this foreign body was found to be lodged in the nasopharynx of the child. The foreign body was removed orally in the out patient department. The patient returned home without any complication.